Multiple Players, Different Tactics, a Shared Goal: Building Bridges and Political Agency While Fighting Against Oil and Gas Drilling - Fernandes-Jesus, Maria; Gomes, Raquel (Frontiers in Communication, 2020)
Several individuals, groups, and organizations have been fighting against oil and natural gas drilling in Portuguese territory. The mobilizations intensified in 2015 in Algarve, and since then 13 concession agreements for oil and gas exploitation, extraction, and production have been canceled. Two concessions for gas drilling remain in Leiria, and this is where the movement is presently more active. Inspired by literature on the role of players and tactics in social movements, as well as on the meanings of agency, we examined how individuals, groups, and organizations contested and demanded the cancellation of the existing concession agreements. We conducted 12 in-depth interviews with highly engaged activists. Based on a thematic analysis, we identified six major themes, named as: “multiple players, a shared goal”; “building bridges with multiple players and tactics”; “links to institutional power”; “the route to the court”; “paths to popular mobilization”; and “movement building and power to act.” Overall, we identified three broad sets of tactics used by the movement, which shows the diversity of players involved in the struggles against oil and gas in Portugal. The first tactic relates to the social movement organizations' efforts to connect with institutional power, either by seeking to pressure local political leaders or by using public consultations, petitions, and other means for expressing their voices. The second tactic refers to the movement's engagement with legal procedures, and the third relates to the movement's efforts to promote popular mobilization. In terms of actions, the movement engaged in protests and public demonstrations, public consultations, public campaigns with celebrities, leaflet distributions, political pressuring of leaders, awareness campaigns in schools and streets, legal actions, among other approaches. All participants described the movement as successful in achieving its shared goal “to cancel oil and gas concessions” and attributed such a success to the movement's ability to combine different strategies and tactics. The movement is also perceived as a setting for building political agency. We discuss the role of the movement in building bridges between multiple players/tactics and in constructing political agency, by focusing on the implications for collective action in environmental and climate issues.